Orchestrating Docker : manage and deploy Docker services to containerize applications efficiently - Holla, Shrikrishna (Community experience distilled., 2015)
Manage and deploy Docker services to containerize applications efficiently In Detail Docker is growing in popularity by day because of its great utility, the fact that it's user friendly, and the vibrant community. This book will help you transform the way you build, test, and deploy your applications with Docker, making it easier and enjoyable. The book starts off with the installation of Docker before gradually taking you through the different commands to start working with Docker containers and their services. You will learn to build your own Docker containers along with instructions to fine-tune the resource allocations to those containers. You will then learn to manage a cluster of Docker containers. The book demonstrates the processes related to the automation and orchestration of Docker. It then covers the compatibility of Docker with other technologies such as Puppet and Chef. Finally, it prepares you to ship your applications without taking strain for deployment. By the end of the book, you will be able to orchestrate and manage the creation and deployment of Docker containers. What You Will Learn Get familiar with the processes related to the automation of Docker Get to grips with various Docker commands and techniques that help you manage containers Create your own Docker image and package your web application in the image Use Dockerfile DSL to make your Docker images repeatable Deploy a high availability service on a cluster using CoreOS and fleet Build your application in sandboxed Docker containers.